Genese e evolucao de um centro produtor textil - Pires, Iva (2021)
In 1981, 72% of the regions active population were employed in the secondary sector, and most of them were working in the woollen industry. The history of the industry is traced from 1881. This industry is now in crisis: with obsolete equipment, the progressive raise in prices of raw materials, and competition of cheaper cotton products, and incapacity of competing in the international market, due to the low quality of products. The integration of the region in the 'Program Local Initiatives of Employment', of the OECD now open new perspectives for development.-from English summary